Placental Injury and Antibody Transfer after Coronavirus Disease 2019 in Pregnancy. (29th June 2022) - Timi, Patience; Kellerhals, Sarah E; Joseph, Naima T; Dude, Carolynn M; Verkerke, Hans P; Irby, Les'Shon S; Smith, Alicia K; Stowell, Sean R; Jamieson, Denise J; Badell, Martina L
Abstract: Background: We examined the relationship between placental histopathology and transplacental antibody transfer in pregnant patients after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Methods: Differences in plasma concentrations of anti-receptor biding domain (RBD) immunoglobulin (Ig)G antibodies in maternal and cord blood were analyzed according to presence of placental injury. Results: Median anti-RBD IgG concentrations in cord blood with placental injury (n = 7) did not differ significantly from those without injury (n = 16) (median 2.7 [interquartile range IQR, 1.8–3.6] vs 2.7 [IQR, 2.4–2.9], P = 0.59). However, they were associated with lower transfer ratios (median 0.77 [IQR, 0.61–0.97] vs 0.97 [IQR, 0.80–1.01], P = 0.05). Conclusions: SARS-CoV-2 placental injury may mediate reduced maternal-fetal antibody transfer.